Kampanye pendidikan anti korupsi - Bekri Reski ,; Dinda Qoneta Soleha ,; Putri Azzahra , (AL-QOLAM : Jurnal Dakwah dan Pemberdayaan Masyarakat, 2022)
In Indonesia, corruption has become a classic story. The government regime has become a double agent. On the one hand, the government promises to eradicate corruption, but on the other hand, the government is also the leading actor. On the other hand, the government is also the primary perpetrator of corruption. This study uses a qualitative descriptive approach. This descriptive study was conducted to examine Indonesia's anti-corruption education campaign in detail. The data collection method used in this research is a literature study. Anti-corruption education can also be understood as a conscious and systematic effort given to students in the form of knowledge, values, attitudes and skills needed so that they are willing and able to prevent and eliminate opportunities for corruption to develop. Campaigning for anti-corruption education by instilling anti-corruption values in students, such as the following values: (1) Honesty, (2) Responsibility, (3) Courage, (4) Justice, (5) Discipline, (6 ) Simplicity, (7) Hard Work, (8) Caring.